Eksplorasi Strategi BKPRMI untuk Meningkatkan Mutu Taman Pendidikan Al-Qur’an sebagai Lembaga Pendidikan Islam Non-Formal - Mujahid, Ahmad Zarkasyi; Afgani, Muhammad Win; Afriantoni (Program Studi Magister Pendidikan Agama Islam, 2024)
The importance of the contribution of an Islamic organization in supporting the progress of Islamic educational institutions, both formal, informal and non-formal so that it affects the quality of learning activities. This study aims to determine the strategy of BKPRMI (Indonesian Mosque Youth and Youth Communication Agency) in improving the quality of TKA-TPA. This research is qualitative research with a case study approach involving the Ministry of Religion of the City of Penukal Abab Lematang Ilir, BKPRI DPK administrators, and 3 TKA-TPA units. Data were collected using interviews and observations and analyzed using data display techniques, data reduction, and verification. The results showed that several strategies carried out by BKPRMI succeeded in improving the quality of TKA-TPA, namely providing socialization to TKA- TPA regarding the application of IJOP (Operational Permit) and BOP (Education Operational Assistance) to the Ministry of Religion, implementing training and standardization of TKA-TPA teachers, proposing incentive funds for village officials and BPJS Employment for TKA-TPA teachers, and carrying out munaqosyah and graduation safaris for students and FASI (Indonesian Salih Children Festival) at the sub-district level. This research has implications for the development of improved management of non-formal institutions in the future. Abstrak Pentingnya kontribusi sebuah organisasi Islam dalam mendukung kemajuan lembaga pendidikan Islam, baik formal, informal maupun nonformal sehingga berpengaruh terhadap kualitas kegiatan pembelajaran. Penelitian ini bertujuan untuk mengetahui strategi BKPRMI (Badan Komunikasi Pemuda dan Remaja Masjid Indonesia) dalam meningkatkan kualitas TKA-TPA. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus yang melibatkan pihak Kementerian Agama Kabupaten Penukal Abab Lematang Ilir, pengurus DPK BKPRMI, dan 3 lembaga TKA-TPA. Data dikumpulkan menggunakan wawancara dan observasi serta dianalisis menggunakan teknik display data, reduksi data, dan verifikasi. Hasil penelitian menunjukkan beberapa strategi yang dilakukan BKPRMI berhasil meningkatkan kualitas TKA-TPA, yaitu memberikan sosialisasi kepada TKA-TPA tentang pengajuan IJOP (Ijin Operasional) dan BOP (Bantuan Operasional Pendidikan) kepada Kementerian Agama, melaksanakan diklat dan standarisasi guru TKA-TPA, mengusulkan dana insentif kepada perangkat desa serta BPJS Ketenagakerjaan untuk guru TKA-TPA, dan melaksanakan munaqosyah dan safari wisuda santri serta FASI (Festival Anak Shaleh Indonesia) tingkat kecamatan. Penelitian ini berimplikasi pada pengembangan manajemen lembaga non-formal ditingkatkan di masa yang akan datang.